Effects of Unloading on Subsequent Yielding Behavior in 304 Stainless Steel - Thrun, Melissa; Finfrock, Christopher; Clarke, Amy; Clarke, Kester (Frontiers in Materials, 2021)
Forming operations are known to be complex, involving many strain states, strain rates, temperatures, strain paths, and friction conditions. Material properties, such as strength and ductility, are large drivers in determining if a material can be formed into a specific part, and for selecting the equipment required for the forming operation. Predicting yielding behavior in situations such as these has been done using yield surfaces to describe material yielding in specific stress states. These models typically use initial mechanical properties, and will require correction if the material has experienced previous straining. Here, we performed interrupted uniaxial tensile testing of a 304 stainless steel to observe the effects of unloading and subsequent reloading on yielding and tensile properties. An increase in yield point developed, in which a higher yield was observed prior to returning to the bulk work hardening behavior, and the magnitude of the yield point varied with unloading conditions and strain imposed. The appearance of a yield point is attributed to strain aging or dislocation trapping at obstacles within the matrix. These results suggest that both strain aging and dislocation trapping mechanisms may be active in the matrix, which may present challenges when forming austenitic stainless and new advanced high strength steels that likely show a similar behavior. These results provide a potential area for refinement in the calculation of yielding criteria that are currently used to predict forming behavior.